3rd AiM International Biennale-A Proposal for Articulating Works and Places by Abdellah Karroum- Exhibition Guide/ (3GdHjfGdj GdOhdj GdKGdK afhf aj eQGcT(B- (3eTQhY aj JfSjb GdCYeGd hGdCeGcf(B- (3Odjd GdeYQV(B- (3JbOje YHOGddg cQhes - AiM International Biennale (Editions Hors' Champs, 2010)
This publication is an inventory of the first part of the exhibition project, A Proposal For Articulating Works and Places, which begins to take shape in Marrakech at Palais Bahia, Theatre Royal, Ecole Superieure des Arts Visuels (ESAV) and other locations. This multistage exhibition project, curated by abdellah Karroum, transforms the exhibition sites into locations of immediate memory that, at the same time, appear elsewhere, beyond the place of the work's presentation. The narratives of the artistic projects explore the connection between the space of production and exhibition. The exhibition creates situations where the artworks occupy and play with the space of a historic monument, Palais Bahia, or move beyond the exhibition space as site-specific projects. Artists intervene in the site of conservation and produce works in symbolic contexts, rendering these Special Projects as sites for visual and aural experimentation in Morocco and abroad. A co-curated film program extends the exhibition and interrogates notions of Freedom? -------------------Artists: Adel Abdessemed, Bani Abidi, Sofia Aguiar, Mustapha Akrim, Francis Alys, Noureddine Amir, Alice Anderson, Younes Baba-Ali, Yto Barrada, Faouzi Bensaidi, Franck Bragigand, Francois Bucher, Chto Delat? (What is to be done?), Tomas Colaco, Claudia Cristovao, Shezad Dawood, Pedro Gomez-Egana, Ninar Esber, Patricia Esqui9vias, Seamus Farrell, Jean-Francois Fourtou, Chourouk Hriech, Isaac Julien, Bouchra Khalili, Hassan Khan, Joseph Kosuth, Faouzi Laatiris, Jooyoung Lee, Loredana Longo, Heidi Nikolaisen,Otobong Nkanga,Kristina Norman, Bouchra Ouizguen, Catherine Poncin, Pere Portabella, Younes Rahmoun, Jerome Schlomoff, Batoul S'Himi, Kathryn Smith, NaoKo TakaHashi, Justine Triet, Nontsikelelo Veleko, James Webb, Hisham Zaman and Sobhi al-Zobaidi.
English; French; Arabic
Keywords: N4390-5098 Visual Arts- Exhibitions